2007
DOI: 10.1186/1471-2180-7-63
|View full text |Cite
|
Sign up to set email alerts
|

Mapping phosphoproteins in Mycoplasma genitalium and Mycoplasma pneumoniae

Abstract: Background: Little is known regarding the extent or targets of phosphorylation in mycoplasmas, yet in many other bacterial species phosphorylation is known to play an important role in signaling and regulation of cellular processes. To determine the prevalence of phosphorylation in mycoplasmas, we examined the CHAPS-soluble protein fractions of Mycoplasma genitalium and Mycoplasma pneumoniae by two-dimensional gel electrophoresis (2-DE), using a combination of Pro-Q Diamond phosphoprotein stain and 33 P labeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 58 publications
3
27
0
5
Order By: Relevance
“…Several of the proteins that are involved in cytadherence in M. pneumoniae are very large proteins, such as HMW1, HMW2, and HMW3. It has been shown that these proteins are phosphorylated in M. pneumoniae (24,33). Therefore, we decided to analyze specifically the phosphorylation pattern of large proteins by using 6% SDS-polyacrylamide gels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of the proteins that are involved in cytadherence in M. pneumoniae are very large proteins, such as HMW1, HMW2, and HMW3. It has been shown that these proteins are phosphorylated in M. pneumoniae (24,33). Therefore, we decided to analyze specifically the phosphorylation pattern of large proteins by using 6% SDS-polyacrylamide gels.…”
Section: Resultsmentioning
confidence: 99%
“…Among these proteins are HMW1 and HMW2, large cytadherence proteins that were shown to be phosphorylated on serine and threonine residues (9,24). Recently, a proteomic approach was used to identify phosphorylated proteins in M. genitalium and M. pneumoniae (33). This study identified 18 phosphoproteins in M. pneumoniae, among them the surface protein MPN474, the cytadherence protein HMW3, and several metabolic enzymes.…”
mentioning
confidence: 99%
“…Phosphoproteins separated by gel electrophoresis can also be visualized by the use of a phosphospecific stain such as Pro-Q Diamond [16][17][18][19]. Alternatively, phosphoproteins can be radioactively labeled using 32 P or 33 P [16,17] and detected by autoradiography, which is the most sensitive method available, but may not be compatible with downstream analytical procedures such as MS. Radioactive labeling is possible both in vivo as well as in vitro. In in vivo studies, cells are incubated with 32 P, however, the presence of endogenous ATP pools within cells can interfere with the incorporation of the label and result in inefficient radioactive labeling [20].…”
Section: Detection Of Phosphoproteinsmentioning
confidence: 99%
“…The minimum set of genes, also called essential genes, in both prokaryotes and eukaryotes, are those described as indispensable for the survival of an organism and are therefore the basis of life for a particular organism. 25 identified only 480 protein-coding regions, while a later study by Ueno et al (2008) 3 found 484 coding regions. These identified coding regions include genes for DNA replication, transcription, translation, DNA repair, cellular transport and energy metabolism.…”
Section: 21mentioning
confidence: 92%